Functional characterization of a wheat NHX antiporter gene TaNHX2 that encodes a K(+)/H(+) exchanger. - Yuanyuan Xu (Public Library of Science (PLoS), 2013)
The subcellular localization of a wheat NHX antiporter, TaNHX2, was studied in Arabidopsis protoplasts, and its function was evaluated using Saccharomyces cerevisiae as a heterologous expression system. Fluorescence patterns of TaNHX2-GFP fusion protein in Arabidopsis cells indicated that TaNHX2 localized at endomembranes. TaNHX2 has significant sequence homology to NHX sodium exchangers from Arabidopsis, is abundant in roots and leaves and is induced by salt or dehydration treatments. Western blot analysis showed that TaNHX2 could be expressed in transgenic yeast cells. Expressed TaNHX2 protein suppressed the salt sensitivity of a yeast mutant strain by increasing its K(+) content when exposed to salt stress. TaNHX2 also increased the tolerance of the strain to potassium stress. However, the expression of TaNHX2 did not affect the sodium concentration in transgenic cells. Western blot analysis for tonoplast proteins indicated that the TaNHX2 protein localized at the tonoplast of transgenic yeast cells. The tonoplast vesicles from transgenic yeast cells displayed enhanced K(+)/H(+) exchange activity but very little Na(+/)H(+) exchange compared with controls transformed with the empty vector; Na(+)/H(+) exchange was not detected with concentrations of less than 37.5 mM Na(+) in the reaction medium. Our data suggest that TaNHX2 is a endomembrane-bound protein and may primarily function as a K(+)/H(+) antiporter, which is involved in cellular pH regulation and potassium nutrition under normal conditions. Under saline conditions, the protein mediates resistance to salt stress through the intracellular compartmentalization of potassium to regulate cellular pH and K(+) homeostasis.